Dante: Traces of the Prophetic - Mfenyana, Deneo Thabisa (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this project is the scrutiny of the vocational claims that Dante makes throughout his Commedia. Engaging the prophet-poet dichotomy through gradations of authorial authority, I place Dante within many vocations from prophet to poet, including mystic, philosopher and theologian, settling ultimately on Dante as a sort of seer, one who communicates parables as The Christ is known to do, but, making it expressly clear that his theological inaccuracies place him beneath biblical prophets in authority. The conscious strategies that Dante employs to secure auctoritas for his poem such as employing the biblical mystical senses, and resting on the shoulders of Virgil his philosophical and poetic auctor will be examined, showing intent in Dante to induce suspension of disbelief in his readers pertaining his vocational claims.
A research thesis submitted in fulfilment of the requirements for the degree of Masters of Arts by Research in English Literature, in the School of within the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in 2023.
Keywords: English literature; Vocational; Auctoritas; Poem; Philosopher; Theologian; UCTD; SDG-4: Quality education